Impact of Intravenous Immunoglobulin on Survival in Necrotizing Fasciitis With Vasopressor-Dependent Shock: A Propensity Score–Matched Analysis From 130 US Hospitals - Kadri, Sameer S.; Swihart, Bruce J.; Bonne, Stephanie L.; Hohmann, Samuel F.; Hennessy, Laura V.; Louras, Peter; Evans, Heather L.; Rhee, Chanu; Suffredini, Anthony F.; Hooper, David C.; Follmann, Dean A.; Bulger, Eileen M.; et al. (Clinical infectious diseases, 2017)
Background. Shock frequently complicates necrotizing fasciitis (NF) caused by group A Streptococcus (GAS) or Staphylococcus aureus. Intravenous immunoglobulin (IVIG) is sometimes administered for presumptive toxic shock syndrome (TSS), but its frequency of use and efficacy are unclear. Methods. Adult patients with NF and vasopressor-dependent shock undergoing surgical debridement from 2010 to 2014 were identified at 130 US hospitals. IVIG cases were propensity-matched and risk-adjusted. The primary outcome was in-hospital mortality and the secondary outcome was median length of stay (LOS). Results. Of 4127 cases of debrided NF with shock at 121 centers, only 164 patients (4%) at 61 centers received IVIG. IVIG subjects were younger with lower comorbidity indices, but higher illness severity. Clindamycin and vasopressor intensity were higher among IVIG cases, as was coding for TSS and GAS. In-hospital mortality did not differ between matched IVIG and non-IVIG groups (crude mortality, 27.3% vs 23.6%; adjusted odds ratio, 1.00 [95% confidence interval, .55–1.83]; P = .99). Early IVIG (≤2 days) did not alter this effect (P = .99). Among patients coded for TSS, GAS, and/or S. aureus, IVIG use was still unusual (59/868 [6.8%]) and lacked benefit (P = .63). Median LOS was similar between IVIG and non-IVIG groups (26 [13–49] vs 26 [11–43]; P = .84). Positive predictive values for identifying true NF and debridement among IVIG cases using our algorithms were 97% and 89%, respectively, based on records review at 4 hospitals. Conclusions. Adjunctive IVIG was administered infrequently in NF with shock and had no apparent impact on mortality or hospital LOS beyond that achieved with debridement and antibiotics.